A novel image integration technology mapping system significantly reduces radiation exposure during ablation for a wide spectrum of tachyarrhythmias in children - He, Jiang; Yi, Zhang; Meiting, Li; Huiming, Zhou; Jinhao, Li; Danlei, Chen; Xiaomei, Li (Frontiers in Pediatrics, 2023)
Objective: Radiofrequency catheter ablation (RFCA) has evolved to an effective and safe technique for the treatment of tachyarrhythmia in children. The issue of radiation exposure to children and involved medical staff should not be ignored during the procedure. “Fluoroscopy integrated 3D mapping”, a new 3D non-fluoroscopic navigation system software (CARTO Univu Module) could reduce fluoroscopy during the procedure. However, there are few studies on children about this new technology. In the study, we analyzed the impact of the CARTO Univu on procedural safety and fluoroscopy in a wide spectrum of tachyarrhythmias as compared with CARTO3 alone. Methods: The data of children with tachyarrhythmia who underwent RFCA from June 2018 to December 2021 were collected. The CARTO Univu was used for mapping and ablation in 200 cases (C3U group) [male/female (105/95), mean age (6.8±3.7) years, mean body weight (29.4±7.9)Kg], and the CARTO3 was used in 200 cases as the control group (C3 group) [male/female (103/97), mean age (7.2±3.9) years, mean body weight (32.3±19.0) Kg]. The arrhythmias were atrioventricular reentrant tachycardia (AVRT, n=78), atrioventricular node reentrant tachycardia (AVNRT, n=35), typical atrial flutter (AFL, n=12), atrial tachycardia (AT, n=20) and ventricular arrhythmias [VAs, premature ventricular complexes or ventricular tachycardia, n=55]. Results: ①There was no significant difference in the acute success rate, recurrence rate, and complication rate between the C3 and C3U groups [(94.5% V.S. 95.0%); (6.3% V.S. 5.3%); (2.0% V.S. 1.5%); P>0.05]. ②The CARTO Univu reduced radiation exposure: fluoroscopy time: AVRT C3: 8.5±7.2 min V.S. C3U: 4.5±2.9 min, P＜0.05; AVNRT C3: 10.7±3.2 min V.S. C3U: 4.3±2.6 min, P＜0.05; AT C3: 15.7±8.2 min V.S. C3U: 4.5±1.7 min, P＜0.05; AFL C3: 8.7±3.2 min V.S. C3U: 3.7±2.7 min, P＜0.05; VAs C3: 7.7±4.2 min V.S. C3U: 3.9±2.3 min, P＜0.05. Corresponding to the fluoroscopy time, the fluoroscopy dose was also reduced significantly. ③In the C3U group, the fluoroscopy during VAs ablation was lower than that of other arrhythmias (P＜0.05). Conclusion: The usage of the “novel image integration technology”, CARTO Univu might be safe and effective in RFCA for a wide spectrum of tachyarrhythmia in children, which could significantly reduce fluoroscopy and has more prominent advantage for VAs ablation.